The Influence of E-wom on Repurchase Intention with Trust As a Mediating Variable (A Case Study of Wearing Klamby) - Nuria Putri; Fatin Hasib (Universitas Pendidikan Indonesia, 2022)
Purpose – This research discusses the influence of E-WOM on Repurchase Intention to Wearing Klamby products. Methodology - The method used is quantitative with Path Analysis for the analysis technique. In the research, the sampling technique used is non-probability sampling, and the non-probability sampling used is the purposive sampling technique. The data used are primary and secondaryFindings - The primary data were obtained by distributing online questionnaires to respondents. The result of this study shows that Trust mediates E-WOM and Repurchase Intention of Wearing Klamby products.Keywords: E-WOM, Trust, Repurchase Intention, Wearing Klamby